2020
DOI: 10.1109/access.2020.2999971
|View full text |Cite
|
Sign up to set email alerts
|

Fuzzy Adaptive Finite-Time Cooperative Control With Input Saturation for Nonlinear Multiagent Systems and its Application

Abstract: In this paper, the fuzzy adaptive finite-time cooperative control with input saturation (FAFTCCIS) is designed to quickly accomplish the cooperation of nonlinear multiagent systems (MASs) without the risk of bumping among agents. At least one agent must communicate with the leader and the information of neighborhood agents is required to accomplish the assigned task. Each agent, including the leader and the followers, is first approximated by N fuzzy-based linear subsystems. To accomplish the null cooperation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 52 publications
(112 reference statements)
0
6
0
Order By: Relevance
“…where 𝜙 i ( q i ) ∈ ℜ n indicates the forward kinematic. By differentiating (20), the below equation is obtained.…”
Section: The Overall Dynamic Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…where 𝜙 i ( q i ) ∈ ℜ n indicates the forward kinematic. By differentiating (20), the below equation is obtained.…”
Section: The Overall Dynamic Systemmentioning
confidence: 99%
“…The system stability is also assured. The fuzzy adaptive control addressed in Reference 20 is applied to accomplish a task that needs the cooperation of planar robots, lacking the collision risk. The aim of Reference 21 is to provide a distributed control strategy for the networked manipulators, which cooperatively move an un‐modeled object in the absence of force measuring requirement.…”
Section: Introductionmentioning
confidence: 99%
“…By known F o , and based on Assumptions 2 and 4, the force F e , satisfying (14), is decomposed into two parts. These parts are orthogonal and correspond to the internal force production and the object transportation as (15) [32,33].…”
Section: Modeling the Object Movementmentioning
confidence: 99%
“…This study also assured the system's stability. A fuzzy adaptive controller was suggested in Hwang et al [15] to carry out a job that needed the cooperation of robots without collision possibility. This study suggested the control/approximation scheme to confront lumped uncertainties and confirm cooperative tasks efficiently.…”
mentioning
confidence: 99%
“…In this article, the advantageous features of nonlinear filtering error with dynamic fraction order include the easy trajectory planning for formation change, the linear dynamics and dynamic fraction order of formation error to shape the frequency response and to achieve fixed-time formation tracking ability [45]- [47]. As the nonlinear filtering error is in the neighborhood of zero, not only the time-varying switching gain increases to accomplish its fixed time convergence but also the fractional learning continues providing the innovative compensation to ensure zero fixed-time formation error in uncertain environments.…”
Section: Introductionmentioning
confidence: 99%